Measuring varietal success on-farm with rank-based metrics - 1000FARMS Platform; van Heerwaarden, Joost (2025)
This one-page brief presents how the 1000FARMS team is developing and validating rank-based indicators to better interpret data from on-farm variety testing using the tricot approach. By analyzing farmers' rankings of different varieties, the team is building new metrics—such as rank agreement, rank distance, and probability of outperforming a reference variety—to capture varietal performance from a user-centered perspective. The metrics allow researchers to compare results across contexts and seasons, and provide a more nuanced picture of success than traditional indicators. The brief explains how these indicators are calculated and shows how they are being applied to multiple datasets, helping breeders and decision-makers make more informed selections based on farmers’ preferences.